An integrated solar cell with built-in energy storage capability. (20th July 2020) - Almakrami, Husain; Wei, Zi; Lin, Guanzhou; Jin, Xinfang; Agar, Ertan; Liu, Fuqiang
Abstract: Due to inherent intermittency nature of light, solar energy must be stored within external batteries in photovoltaic systems, resulting in systems that are fragile and expensive. Internal storage integration can offer highly robust systems at substantially low cost if external batteries are replaced by internal ones. Despite excellent photovoltaic power conversion efficiencies of dye-sensitized solar cells, they are short of storage capability. In this work, we demonstrate an integrated solar storage cell that can potentially deliver solar power even in darkness owing to its integrated energy storage capability. The cell was built upon the dye-sensitized solar cell platform using a photochromic WO3 electrode and had the ability to simultaneously generate and store charges during the day and discharge the stored charges during night. Specifically, three different batches of WO3 nanoparticles, each of unique particle size, were investigated in terms of their compatibility with the solar storage cell and built-in storage capacity. Our results revealed that the solar storage cell with the largest WO3 particle size (∼100 nm) exhibited the best transient voltage-current characteristics. On the other hand, intermediate WO3 particle size (60–95 nm) displayed the best storage capacity when undergoing a prolonged photocharging. These comparative investigations shed light on the morphological difference in electrode, active surface area, porosity-dependent electron transport, and redox diffusion coefficient that have a significant impact on the photo/electrochemical properties of the electrodes. Graphical abstract: Image 1